What Every Therapist Needs to Know About Couple Therapy. Issue 3 (26th September 2019) - Halford, W. Kim; Pepping, Christopher A.
Abstract: This invited paper is a review of the significance of couple relationships to the practice of all therapists. The article begins with a summary of the evidence on the centrality of committed couple relationships to the lives and wellbeing of adults, and the association of the quality of the parents' couple relationship on the wellbeing of children. We argue that the well-established reciprocal association between individual problems and couple relationship problems means that all therapists need to pay attention to how a couple relationship might be influencing a client's functioning, even if the relationship is not the presenting problem. There is an outline the evolution of current approaches to behavioural couple therapy, and the current state of the art and science of couple therapy. We present an analysis of the evidence for couple therapy as a treatment for relationship distress, as well as couple-based treatments for individual problems. This is followed by a description of the distinctive challenges in working with couples and how to address those challenges, and recommendations about how to address the needs of diverse couple relationships. Finally, we propose some core therapist competencies needed to work effectively with couples.